Ventricular synchrony in artificial cardiac pacing: The role of the helical myocardium and fulcrum in the electromechanical coupling of the heart - Ventura, Alejandro; Viola, Luciana; Ferrari, Andrés Di Leoni (Seven Editora, 2023)
About 30% of patients with Heart Failure (HF) have wide QRS complexes. In left bundle branch block (LBBB), the electromechanical activation sequence in the Left Ventricle (LV) is asynchronous with deterioration of pump function, higher frequency of hospitalizations and mortality. Definitive artificial cardiac stimulation, especially when from the apex of the Right Ventricle (RV), entails ventricular activation identical and as antiphysiological as LBBB, and therefore, in a percentage of cases, a worsening of the degree of HF and a higher incidence of arrhythmias occurs. headphones, hospitalizations, and mortality. In search of “physiological” stimulation, alternative RV electrode placement sites (non-apical sites) have been evaluated. We highlight the stimulation of the bundle of His, the area of the left branch, or biventricular stimulation for cardiac resynchronization, strategies included in a generic term: Cardiac Physiologic Pacing – CPP (1) and with promising results in preserving and/or restoring synchrony. cardiac electromechanics. However, due to the complexity of the procedures, especially technical and resources, the first two have not had the consensus or the expected growth. On the other hand, biventricular Cardiac Resynchronization Therapy (CRT) was also shown to be ineffective in about 30% of patients (non-responders). Dr. Francisco Torrent Guasp, demonstrated that the ventricular myocardium is made up of a continuous muscular band with a helical shape, which explains the great efficiency of cardiac systole, where blood is expelled through torsion-detorsion contraction mechanisms, with a phase active suction in protodiastole. The cardiac fulcrum functions as a fulcrum and support for the helical myocardium. According to this author, the propagation of the electrical stimulus and the contraction of the myocardium (electromechanical coupling) begin in the region of the right ventricular outflow tract (RVOT) anatomically related to the cardiac fulcrum, advancing towards the rest of the helical myocardial segments and continuing the longitudinal direction of the muscle bundles, which could explain the results of definitive cardiac pacing in the RVOT septum with electrical synchrony in some cases. Synchromax® (Exo S.A., Buenos Aires, Argentina) is a software which records non-invasively during lead implantation: spatial coincidence, area and direction of QRS in leads D2 and V6 from the ECG. Intraoperatively, after analysis and in real-time, generates a mathematical index called cross-correlation cardiac synchrony index (CSI) which at this time generates a couple of synchrony curves. A CSI value of 0.0 corresponds to maximum coincidence between both leads (perfect ventricular synchrony), 0.0-0.39 demonstrate adequate synchrony, 0.4-0.7 equal poor synchrony, and values > 0.71 correspond to cardiac dyssynchrony. In this chapter we present a new perspective. An anatomical-mechano-physiological vision in which the coordination of cardiac activity is based on the interdependence between structure, activation and function: cardiac synchrony. In this context, physiological cardiac stimulation seeks to artificially reproduce that the result is, as in nature, maximum electromechanical coordination with the goal of the best cardiac systolic function. As will be explained, it is difficult to explain efficient and coordinated (synchronous) cardiac performance without an adequate structure, or to accept a non-complex anatomy for the competent development of the function. DOI:https://doi.org/10.56238/innovhealthknow-029